Level of Effectiveness of Reading Comprehension Ability of Grade VII Students of SMP Negeri 1 Tilango - Robbiyana Lasomba; Sayama Malabar; Puspita Dian Agustin (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Reading comprehension is a basic skill that plays an important role in supporting student learning success, especially at the junior high school level. However, various findings show that students’ reading comprehension skills are still relatively low. This study aims to describe the reading comprehension skills and Reading Effectiveness Skills (KEM) of seventh grade students at SMP Negeri 1 Tilango. This study uses a quantitative descriptive design. There were 26 seventh-grade students participating in this study. Data were collected through a KEM-based reading test that measured reading speed and reading comprehension, as well as interviews as supporting data. Data analysis was conducted by calculating reading speed (words per minute), reading comprehension percentage, and KEM scores obtained from the multiplication of these two components. The results of the study show that the average reading speed of seventh grade students at SMP Negeri 1 Tilango is 113 wpm with an average comprehension level of 63%. The average KEM score obtained by students is 74 wpm. Based on the KEM category, 80.8% of students were in the ineffective category and only 19.2% of students reached the fairly effective category. These findings indicate that the reading comprehension skills of seventh grade students at SMP Negeri 1 Tilango are still low and there is an imbalance between reading speed and comprehension of reading content. Therefore, more focused and continuous reading learning efforts are needed to improve the effectiveness of student reading.